MODERN APPROACHES TO IMPROVING CREDIT OPERATIONS IN COMMERCIAL BANKS (International Congress on Economics, Management and Business Studies, 2026)
This study examines the contemporary approaches to enhancing credit operations in commercial banks based on international banking practices and academic literature. The research highlights the importance of effective credit policies, advanced risk assessment procedures, efficient credit portfolio management, digital technologies, and continuous monitoring of lending activities. The findings indicate that a comprehensive approach combining sound lending principles, technological innovation, and effective management practices contributes to improving the quality and sustainability of bank credit operations.
Keywords: commercial banks, credit operations, lending activities, credit management, banking efficiency, digital transformation, credit policy, financial stability.